Investigation of inflammatory effects of dexmedetomidine and sugammadex in early wound healing in rats (Annals of Medical Research, 2023)
Aim: The aim of this study was to determine how local dexmedetomidine and sugammadex application affect TNF- α IL-1β levels, and histopathological scores, which are important markers of inflammatory response, in a rat experimental wound model.Materials and Methods: In Group D, 2 ml of 10 mcg diluted dexmedetomidine (n=8), 2 ml of 10 mg diluted sugammadex (n=8), and 2 ml of saline (n=8) were infiltrated into the incision lips. Plasma TNF-α, IL1-β levels was measured. The rats were awakened. Their survival was continued for 7 days. On the seventh day following the procedure, a biopsy was taken from the subjects' incision line, and their histopathological wound healing scores were evaluated.Results: There was a difference between the mean values of TNF-α between the groups (p=0.016). TNF-α was found to have a mean value of 299.59 in the control group, 253.41 in the dexmedetomidine group, and 249.51 in the sugammadex group. IL-1β values, chronic inflammation (CI), granulation (G) and fibrosis (F) scores did not differ between groups (p values ​​0.752, 0.118, 0.368, and 0.296, respectively). The active inflammation (AI) scores of the all groups differed significantly (p=0.007).Conclusion: Dexmedetomidine and sugammadex have been shown to accelerate the migration of polymorphous core leukocytes to the wound site. We believe that our research will shed light for future clinical trials.
Keywords: Wound healing; Rat; Dexmedetomidine; Sugammadex